Mother imagery in the novels of Afro-Caribbean women - Alexander, Simone A. James, 1967- (University of Missouri Press, 2001)
"Focusing on specific texts by Jamaica Kincaid, Maryse Conde, and Paule Marshall, this study explores the intricate trichotomous relationship between the mother (biological or surrogate), the motherlands Africa and the Caribbean, and the mothercountry represented by England, France, and/or North America. The mother-daughter relationships in the works discussed address the complex, conflicting notions of motherhood that exist within this trichotomy. Although mothering is usually socialized as a welcoming, nurturing notion, Alexander argues that alongside this nurturing notion there exists much conflict. Specifically, she argues that the mother-daughter relationship, plagued with ambivalence, is often further conflicted by colonialism or colonial intervention from the "other," the colonial mothercountry." "Mother Imagery in the Novels of Afro-Caribbean Women offers an overview of Caribbean women's writings from the 1990s, focusing on the personal relationships these three authors have had with their mothers and/or motherlands to highlight links, despite social, cultural, geographical, and political differences, among Afro-Caribbean women and their writings. Alexander traces acts of resistance, which facilitate the (re)writing/righting of the literary canon and the conception of a "newly created genre" and a "womanist" tradition through fictional narratives with autobiographical components."--Jacket.